2014
DOI: 10.2350/14-03-1452-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Gene Polymorphisms (GSTM1, GSTT1, and GSTP1) in Egyptian Pediatric Patients with Sickle Cell Disease

Abstract: Sickle cell disease (SCD) complications are associated with oxidative stress. Glutathione S-transferases (GSTs) are a group of enzymes that protect against oxidative stress. The aims of this study was to evaluate the prevalence of GSTM1, GSTT1, and GSTP1 gene polymorphisms among homozygous sickle cell anemia patients and to investigate the possible association between the presence of these polymorphisms and SCD severity and complications. Genotyping the polymorphisms in GSTT1 and GSTM1 genes was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“… 30 However, similar allele frequencies and genotype distribution of this polymorphism were found in 50 Egyptian SCA patients and healthy controls in another study. 31 Higher frequency of 105Val polymorphism among β-thalassemia patients detected in this work and among SCA patients in the previous Brazilian study 30 compared to the healthy controls may suggest genetic linkage between, GSTP1 gene (11q13) and β-globin gene (11p15).…”
Section: Discussionsupporting
confidence: 44%
“… 30 However, similar allele frequencies and genotype distribution of this polymorphism were found in 50 Egyptian SCA patients and healthy controls in another study. 31 Higher frequency of 105Val polymorphism among β-thalassemia patients detected in this work and among SCA patients in the previous Brazilian study 30 compared to the healthy controls may suggest genetic linkage between, GSTP1 gene (11q13) and β-globin gene (11p15).…”
Section: Discussionsupporting
confidence: 44%
“…reported the association of the null GSTT1 genotype with an increased need for blood transfusions. However, Shiba et al (2014) did not find that association. also reported the association between the GSTT1 polymorphism and acute thoracic syndrome and vaso-occlusion crises.…”
Section: Resultsmentioning
confidence: 76%
“…also reported the association between the GSTT1 polymorphism and acute thoracic syndrome and vaso-occlusion crises. Shiba et al (2014) reported that the complications related to SCA are associated with the intense process of oxidative stress, and the GST enzymes protect the body from oxidative stress. They found no significant association between the null genotypes and the frequencies of pain related to SCA, blood transfusion, disease severity or treatment with hydroxyurea.…”
Section: Resultsmentioning
confidence: 99%
“…Several epidemiological studies have reported that the GSTT1 null genotypes results in a lack of functional protein which may cause increased vulnerability to oxidative DNA damage and excessive ROS generation and may ultimately result in increased susceptibility to various diseases associated with oxidative stress including SCD. 22 The distribution of GSTM1 and GSTT1 null genotypes varies among different ethnic groups. Several population-based studies have reported a prevalence ranging from 47 to 58% for the GSTM1 null genotype and from 13 to 25% for the GSTT1 null genotype among white Europeans 23 and 27.6% among the US white population.…”
Section: Discussionmentioning
confidence: 99%